Genesis of the Investigatory Actions of Criminal Procedure of the Republic of Kazakhstan - KALKAMANULY, Daniyar (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The present article analyzes the history of the development of investigatory actions on the territory of the modern Kazakhstan since the force of ordinary law of the nomad tribes till the modern regulation of investigatory actions according to the Criminal Procedure Code of the Republic of Kazakhstan of 2015. Despite the deep scientific research of the institution of the investigatory actions in many scientific studies, there are still some unsolved questions regarding the investigatory actions. Thus, very little attention is paid by the scholars-processualists to the problem of evolution of the investigatory actions from their sources to the modern legislative regulation. This problem was considered only partially and is not a direct subject of the complete research. At the same time, the analysis of the development of the investigatory actions based upon the scientific works and legislation acts regulating the criminal procedure legal relations allows to summarize and systematize the scientific approaches to the development and improvement of the investigatory actions, which, in its turn, allows to consider the issue of tendencies and perspectives of the development of this institution. Taking into account the above stated, the aim of the research of the article is a complex analysis of the criminal procedure law of the prerevolutionary, Soviet and modern periods, the determination of the main tendencies on this basis and perspectives of the development of the institution of investigatory actions and formulation of the theoretical and scientific and practical provisions and conclusions concerning its improvement. According to the aim set, the article presents the historical and legal analysis of the development of the investigatory actions in the criminal procedure law of Kazakhstan; the legal essence of the changes of the institution of the investigatory actions is determined in the various historical periods; the proposals to improve the rules of procedure regulating the investigatory actions procedure were developed. The article proves the possibility of solving the modern problems of the regulation of the investigatory actions due to the use of the advanced achievements of the science and fundamental developments of the distinguished scholars-processualists.